2001
DOI: 10.1677/joe.0.1680163
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory effect of experimental diabetes on the expression of endothelin receptor subtypes and their gene transcripts in the rat adrenal gland

Abstract: Endothelins (ETs) mediate paracrine control of vascular tone and secretion of steroids and catecholamines in the adrenal gland through two ET receptor subtypes, ETA and ETB. The differential distribution and function of these subtypes are responsible for the multiplicity of endothelin actions in this tissue. This study examines the regulatory effects of experimental diabetes on the gene expression, subtype specificity and localization of ET receptor subtypes, ET isopeptides, and endothelinconverting enzyme-1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…However ET B receptors, located on VSM, produce effects akin to the ET A (Schneider et al, 2007;Pollock, 2010). Mounting evidence suggests that the balance of these receptors within the vasculature may be tipped toward the contractile ET B phenotype under pathological circumstances (Ikeda et al, 2001;Stenman et al, 2002;Alabadi et al, 2004;Matsumoto et al, 2004;Ortmann et al, 2004). We have demonstrated previously that chronic blockade of the ET A receptor in type 2 diabetes decreases vascular remodeling by attenuation of MMP dysregulation .…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…However ET B receptors, located on VSM, produce effects akin to the ET A (Schneider et al, 2007;Pollock, 2010). Mounting evidence suggests that the balance of these receptors within the vasculature may be tipped toward the contractile ET B phenotype under pathological circumstances (Ikeda et al, 2001;Stenman et al, 2002;Alabadi et al, 2004;Matsumoto et al, 2004;Ortmann et al, 2004). We have demonstrated previously that chronic blockade of the ET A receptor in type 2 diabetes decreases vascular remodeling by attenuation of MMP dysregulation .…”
Section: Introductionmentioning
confidence: 80%
“…at ASPET Journals on May 12, 2018 jpet.aspetjournals.org the diabetic rabbit urinary bladder, whereas Ikeda et al (2001) showed a significantly increased ET B gene expression in streptozotocin diabetic rat adrenal glands. Most notably, contractile ET B receptors are up-regulated in rat MCAs after focal cerebral ischemia (Henriksson et al, 2003).…”
Section: Cerebrovascular Remodeling and Et Receptors In Diabetes 13mentioning
confidence: 89%
“…Indeed, it has been demonstrated that diabetes does upregulate vascular ET B receptor expression. Ikeda et al (23) found increased ET B receptor density in the diabetic rabbit urinary bladder, while Ortmann et al (41) showed a significantly increased ET B gene expression in STZ diabetic rat adrenal glands. In 10-wk-old NOD mice, a Type 1 diabetes model, aortic ET B gene expression was significantly increased while ET A expression was unchanged (41).…”
Section: ) and Magnitude (R Max ) Of Vascular Responses To Et-1 And Amentioning
confidence: 99%
“…To ensure a fixed amount of initial mRNA in parallel with GAPDH, amplification was performed using the following oligonucleotides: Sense: 5V-GCTGGGGCTCACCTGAAGG-3V, Antisense: 5V-GGATGACCTTGCCCACAGCC-3V. Specific oligonucleotide primers were used in this experiment according to the references as below: RyR2 [17], PKA [18]; ECE (endothelin-converting enzyme) [19]; PreproET-1 (prepro-endothelin-1) [20]. Density of the bands was analyzed with Labworks imaging acquisition and analysis software.…”
Section: Cardiac Gene Expressionmentioning
confidence: 99%